American Factor in Inter-Korean Relations in 2012-2023 - Evgenia Yu. Katkova; Anna I. Glushchenko (RUDN Journal of World History, 2024)
The relevance of the research topic is due to the active development of the U.S.-South Korean relations and their impact on inter-Korean relations. The role of the United States in the foreign policy of the Republic of Korea is great which not only limits it in developing of its own potential due to the direct dependence on decisions and actions but also hinders the normalization of relations between the two Koreas. The purpose of the research is to examine the dynamics of relations in the triangle ‘‘ROK (Republic of Korea) - DPRK (Democratic People’s Republic of Korea) - U.S.”. The main methods of the study include analyzing the events in the triangle ‘‘ROK - DPRK - the U.S.” as well as the texts of UNSC (United Nations Security Council) resolutions on nuclear non-proliferation on the Korean peninsula. The study concludes that despite South Korea’s attempts to stabilize relations with its northern neighbor, its pro-American course in foreign policy has prevented it from making significant concessions. For today, the ROK’s foreign policy is aimed at deepening cooperation with the US and its security partners in the region. Therefore no warming in relations between the two Koreas is expected in the near future.